2022
DOI: 10.1177/0271678x221127088
|View full text |Cite
|
Sign up to set email alerts
|

Expedited brain cooling: Persistent temperature management from first aid to interhospital treatment

Abstract: Selective brain cooling is a promising technique for improving outcomes in ischemic stroke in the area of reperfusion. A recent study described the efficacy of a new method of selective brain cooling via active conductive head cooling. This is a major step forward in the administration of hypothermic treatment during pre-hospital transfer. However, to enhance the benefits of selective therapeutic cooling, a more comprehensive strategy preventing delay in hypothermic induction and increasing the accuracy of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…So although intraarterial cooling may be effective at inducing penumbral hypothermia, adjunctive methods to induce penumbral cooling in the minutes or hours leading up to EVT, and to slow rewarming after cessation of intraarterial cooling are required. 6…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So although intraarterial cooling may be effective at inducing penumbral hypothermia, adjunctive methods to induce penumbral cooling in the minutes or hours leading up to EVT, and to slow rewarming after cessation of intraarterial cooling are required. 6…”
Section: Discussionmentioning
confidence: 99%
“…So although intraarterial cooling may be effective at inducing penumbral hypothermia, adjunctive methods to induce penumbral cooling in the minutes or hours leading up to EVT, and to slow rewarming after cessation of intraarterial cooling are required. 6 Intravenous cooling resulted in penumbral temperatures of 35.4-35.8 C. Previous studies have shown that intravenous cooling may be effective at inducing and maintaining modest hypothermia but is practically difficult to administer. Intravenous cooling is also an indirect method of cooling the penumbra as it requires the induction of systemic hypothermia to remove heat from the non-ischemic and ischemic brain tissue, and this can lead to significant side effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as other cytoprotective treatments, ice helmets have not been successfully applied in clinical trials to generate neuroprotection without reperfusion in previous studies. [ 20 ] After highly effective reperfusion therapy is widely available and the cooling rate is successfully improved, as adjuvant treatments to thrombolysis or endovascular thrombectomy, cooling helmets are promising to be neuroprotective for AIS.…”
Section: Surface Brain Coolingmentioning
confidence: 99%